Idiopathic toe walking: What’s New? An Integrative Review: An Integrative Review - Santos, Letícia D’Ordaz Lhano; Oliveira Generoso, Talissa; Angeli, Luiz Renato Agrizzi de; Blumetti, Francesco Caamara; Barcelos, Filipe Machado (Journal of the Foot & Ankle, 2024)
Objective: Consolidate the current knowledge on idiopathic toe walking, provide a critical overview, and identify areas for potential future research. Methods: An electronic search was conducted in the following databases up to June 2023: MEDLINE, EBSCO, Embase, CINAHL Plus, and PubMed. The PICO framework was employed to define search terms. Results: Despite considerable methodological heterogeneity among studies, a stronger inclination was found to investigate etiological and prognostic factors. There is a trend for a higher prevalence in boys with a positive family history. Novel classifications have been proposed to improve differential diagnosis. Among conservative treatment options, there is stronger evidence for gait improvement using serial casting followed by orthoses. Severe cases may benefit from surgical zone III gastrocsoleus lengthening. Conclusion: Further studies with standardized methodologies are required to clarify questions about this condition’s etiology, classification, and treatment. Nonetheless, there is a higher level of evidence supporting conservative treatments with serial casting and orthoses and zone III gastrocsoleus lengthening for severe cases in the second decade of life. Level of evidence II; Diagnostic studies. Keywords: Walking; Equinus Deformity; Foot;